Mechanical Analysis of Stretchable AlGaN/GaN High Electron Mobility Transistors. (25th April 2016) - Tompkins, Randy P.; Mahaboob, Isra; Shahedipour-Sandvik, Shadi; Lazarus, Nathan
Abstract : Adding waves or kinks to a conductor is a well-known method for relieving strain in stretchable systems. Although transistors and other devices made of brittle semiconductors have also been demonstrated, the effects of the crystalline anisotropy on the mechanical behavior has not been previously investigated. In this work, a numerical solver is used to simulate the peak stresses in silicon and gallium nitride embedded within soft silicone in common stretchable geometries. As expected from other work, adding waves reduces peak stress by more than a factor of ten. The effects of in-plane rotations were then investigated. In the typical [0001] growth direction for gallium nitride, the matrix is rotationally invariant, with no variation in peak stress upon rotation about the [0001] direction. For silicon, however, peak stress was found to vary by as much as 17 percent for rotation about the [001] direction.